Glanzmann thrombasthenia: deficient binding of von Willebrand factor to thrombin-stimulated platelets. - Ruggeri, Z M (1982)
Glanzmann thrombasthenia is an inherited bleeding disorder characterized by the failure of platelets to aggregate in response to almost all stimuli. However, thrombasthenic platelets will aggregate with bovine and porcine von Willebrand factor (vWF) and will show normal ristocetin-induced binding and aggregation in the presence of human vWF. In contrast, we now report that the specific binding of vWF to the thrombin-stimulated platelets was less than 20% of normal in three patients with Glanzmann thrombasthenia. Analysis of binding isotherms was based on the assumption of one class of binding sites for vWF on the platelet membrane. Double-reciprocal plots were used to calculate maximal binding at saturation and apparent dissociation constant (Kd). In nine normals, 2.82 +/- 0.64 micrograms (+/- SD) of vWF bound to 10(8) platelets at saturation, with Kd (+/- SD) = 3.65 +/- 1.23 micrograms/ml. In two patients with thrombasthenia binding was markedly decreased and did not approach saturation. In the third patient, binding at saturation corresponded to 0.21 micrograms per 10(8) platelets, with Kd = 3.93 micrograms/ml. These findings suggest that mechanisms underlying the vWF-platelet interaction are incompletely reflected in ristocetin-dependent assay systems. Moreover, these results, in addition to those previously reported for fibronectin, suggest that the platelet defect in Glanzmann thrombasthenia is not limited to decreased binding of fibrinogen but involves several glycoproteins that are known to interact with platelets.